2022
DOI: 10.1002/admt.202200329
|View full text |Cite
|
Sign up to set email alerts
|

La2NiO4+δ‐Based Memristive Devices Integrated on Si‐Based Substrates

Abstract: Valence Change Memories, in which internal redox reactions control the change in resistance are promising candidates for resistive random access memories (ReRAMs) and neuromorphic computing elements. In this context, La2NiO4+δ (L2NO4), a mixed ionic-electronic conducting oxide, well known for its highly mobile oxygen interstitial ions, emerges as a potential switching material for novel L2NO4-based memristive devices. However, their integration in complementary metal oxide semiconductor (CMOS) technology still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…[3,10] On top of that, VCMs can be used for neuromorphic computing, where the device itself shows the behavior that is typically hardcoded in most AI applications, and hence, VCMs may present larger storage density and lower power consumption in applications such as those involving AI. [11][12][13] In our previous work, we studied pure LaMnO 3+δ , and proved that it was possible to change the resistance state up to two orders of magnitude by oxygen drift and by the concomitant redox reactions taking place at the materials' surface, as experimentally proven by combining conductive atomic force microscopy with X-ray photoemission electron spectroscopy Valence change memories are novel data storage devices in which the resistance is determined by a reversible redox reaction triggered by voltage. The oxygen content and mobility within the active materials of these devices play a crucial role in their performance.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…[3,10] On top of that, VCMs can be used for neuromorphic computing, where the device itself shows the behavior that is typically hardcoded in most AI applications, and hence, VCMs may present larger storage density and lower power consumption in applications such as those involving AI. [11][12][13] In our previous work, we studied pure LaMnO 3+δ , and proved that it was possible to change the resistance state up to two orders of magnitude by oxygen drift and by the concomitant redox reactions taking place at the materials' surface, as experimentally proven by combining conductive atomic force microscopy with X-ray photoemission electron spectroscopy Valence change memories are novel data storage devices in which the resistance is determined by a reversible redox reaction triggered by voltage. The oxygen content and mobility within the active materials of these devices play a crucial role in their performance.…”
mentioning
confidence: 94%
“…The memristive properties of LSM50 are studied using titanium as an active electrode. As for other material combinations, [3,11,13,[33][34][35][36][37][38][39] the Ti/LSM50 stack can undergo a reversible redox reaction that originates two additional interlayers: oxidized metal electrode and oxygen-deficient oxide. The resistivity of both interlayers is higher than the parent compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported on the VCM capabilities of memristive devices based on La 2 NiO 4+δ (L2NO4), a perovskite-related structure, using an ohmic Pt electrode and an active (i.e. easily oxidizable) Ti counter electrode (forming a rectifying and tunable Schottky contact) [38,39]. L2NO4 was selected as mixed ionic electronic conducting (MIEC) oxide due to its high oxygen mobility [40,41] able to facilitate the storage and exchange of oxygen with the active electrode material (Ti).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the previously mentioned L2NO4 planar memristive devices were successfully transferred to vertical Ti/L2NO4/Pt structures [39]. Nevertheless, these devices still presented certain cycle-to-cycle (c2c) and device-todevice (d2d) variability and resistance relaxation with time.…”
Section: Introductionmentioning
confidence: 99%